G109 Depression, anxiety and health related quality of life in paediatric non-alcoholic fatty liver disease; under-recognised and under-managed?. (May 2019) - Makin, I; Samyn, M; Day, J; Tizzard, S; Paul, B; Mortimer, H; Fitzpatrick, E
Abstract : Aims: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in children and young people (CYP) and is the hepatic manifestation of metabolic syndrome. Prevalence of mental health disorders in this population is unknown. Our aim was to define the prevalence of depression and anxiety and assess health related quality of life (HRQL) in a cohort of children with NAFLD and investigate clinical correlates. Methods: We audited CYP attending a NAFLD clinic in a tertiary paediatric liver unit over a 6 month period. Data were collected using PedsQL, validated to assess HRQL in CYP, and the screening tool RCADS (Revised Children's Anxiety and Depression Score). Results: During the study period, 43 parent-CYP pairs (24 boys) completed questionnaires. Median age at presentation was 12.7 years (IQR 11.3, 14.3). Median age at questionnaire was 14.7 y (IQR 13.5, 16.3) when median BMI was 31.2(IQR 26.4, 36.2). PedsQL data are presented in table 1 . In CYP with NAFLD, 47% were >1 SD below the mean of healthy controls, compared to CYP with biliary atresia where 29.5% scored >1 SD below the mean. 2 Using RCADS; 36% percent of CYP with NAFLD (44% parent report) scored in the borderline range for depression, and 19% (25% parent report) for anxiety, compared to 7% in general population norms. Six percent of CYP with NAFLD (17% parent report) scored in the range for depression, and 3% (6% parent report) for anxiety, relative to 2% in the general population. There was no statistical association between BMI, sex, age, splenomegaly, weight gain and either anxiety or depression score. Conclusion: There is a high prevalence of depression and anxiety and associated poor quality of life in CYP with NAFLD. Further work will explore impact of mental health on outcome. References: Sundaram, et al. 2013. D'Avila, et al. 2018.